Geological Hazard Potential Using Scoring And Weighting Method In Citeureup Sub-watershed, Citeureup District And Surrounding Area, Bogor Regency - Adji, Andika Rhadiya Putra; Iskandarsyah, Teuku Yan Waliana Muda; Listiawan, Yudhi (Faculty of Geological Engineering, Universitas Padjadjaran, 2024)
Geological hazards are hazard caused by geological processes. Citeureup Sub-watershed, located in Bogor Regency, is a densely populated area threaten by geological hazards. The purpose of this study is to determine the distribution of geological hazards using scoring and weighting method. Factors that analyzed to determine hazards potential including: slope, rocks physical property, lineament density, and rainfall. Hazard potential in study area divided into five different levels, ranging from very low to very high, with geological hazards in the form of mass movement and earthquake. Main factor of mass movement hazard potential is slope, meanwhile earthquake potential hazard main factor is lineament density, which indicates geological structure. Rocks physical property and rainfall are supporting factors that can increase geological hazards potential.